A microemulsion of puerarin–phospholipid complex for improving bioavailability: preparation, in vitro and in vivo evaluations. (3rd August 2018) - Wu, Jun-Yong; Li, Yong-Jiang; Han, Meng; Hu, Xiong-Bin; Yang, Le; Wang, Jie-Min; Xiang, Da-Xiong
Abstract: Puerarin is a phytochemical with various pharmacological effects, but poor water solubility and low oral bioavailability limited usage of puerarin. The purpose of this study was to develop a new microemulsion (ME) based on phospholipid complex technique to improve the oral bioavailability of puerarin. Puerarin phospholipid complex (PPC) was prepared by a solvent evaporation method and was characterized by X-ray diffraction and infrared spectroscopy. Pseudo-ternary phase diagrams were constructed to investigate the effects of different oil on the emulsifying performance of the blank ME. Intestinal mucosal injury test was conducted to evaluate safety of PPC-ME, and no sign of damage on duodenum, jejunum and ileum of rats was observed using hematoxylin-eosin staining. In pharmacokinetic study of PPC-ME, a significantly greater C max (1.33 µg/mL) was observed when compared to puerarin ( C max 0.55 µg/mL) or PPC ( C max 0.70 µg/mL); the relative oral bioavailability of PPC-ME was 3.16-fold higher than puerarin. In conclusion, the ME combined with the phospholipid complex technique was a promising strategy to enhance the oral bioavailability of puerarin.